Illuminating the dynamic water–nitrogen relationship in rice via stable isotope techniques to improve cultivation - Linlin Jiang; Bin Yang; Fan Zhao; Jie Pan; Zhenjie Chen; Junen Wu (Agricultural Water Management)
Rice is a staple food for more than half of the global population, and optimizing water and nitrogen (N) management is crucial for sustainable rice production. This study investigated the water uptake patterns, agronomic traits, and quality indicators of two rice varieties (Yanfeng 47, high N efficiency and Yanggengnuo 66, low N efficiency) under four N fertilizer treatments via a split-plot design at Shenyang Agricultural University’s Rice Research Institute Experimental Base in Shenyang, Liaoning Province, China. Stable isotope analysis and modeling approaches were used to quantify the proportional contributions of various water sources to rice water uptake, considering both isotope discrimination and memory effects. Both N levels and genetic differences significantly influenced rice water uptake behavior, primarily through the functional characteristics of the root system. The high-efficiency variety presented a well-developed root system with a stable water uptake pattern, whereas the low-efficiency variety presented relatively greater root plasticity and N sensitivity. The presence of a memory effect suggests that rice water uptake could be more dependent on both the current and past water status, not simply the current external water conditions. After the memory effect was corrected, irrigation water was the dominant water source for rice, followed by soil water and rainwater. Agronomic traits and quality indicators were also differentially sensitive to variety and N treatments. Root traits were differentially influenced by N level and variety, with less efficient varieties showing greater sensitivity. In addition to root traits, leaf length, plant height and panicle traits were greater in the low-efficiency variety. N application generally increased yield, but excessive N negatively affected yield, especially in high-efficiency varieties. Our findings contribute to the understanding of waternitrogen interactions in rice and emphasize the importance of the process-based water use efficiency of individual varieties and variety-specific management in the future for more efficient use of nutrients for growing rice with high yield and quality. This study sheds light on the underlying mechanisms responsible for varietal sensitivity to water and N and provides opportunities for optimizing proper management with precision.